Britain's War Machine : weapons, resources and experts in the second world war - Edgerton, David (UK: Penguin Books, 2012)
"The familiar image of the British in the Second World War is that of the plucky underdog taking on German might. David Edgerton's bold, compelling new history shows the conflict in a new light, with Britain as a very wealthy country, formidable in arms, ruthless in pursuit of its interests, and in command of a global production system. Rather than belittled by a Nazi behemoth, Britain arguably had the world's most advanced mechanized forces. It had not only a great empire, but allies large and small. Edgerton shows that Britain fought on many fronts and its many home fronts kept it exceptionally well supplied with weapons, food and oil, allowing it to mobilize to an extraordinary extent. It created and deployed a vast empire of machines, from the humble tramp steamer to the battleship, from the rifle to the tank, made in colossal factories the world over. Scientists and engineers invented new weapons, encouraged by a government and prime minister enthusiastic about the latest technologies. The British, indeed Churchillian, vision of war and modernity was challenged by repeated defeat at the hands of less well-equipped enemies. Yet the end result was a vindication of this vision. Like the United States, a powerful Britain won a cheap victory, while others paid a great price. Putting resources, machines and experts at the heart of a global rather than merely imperial story, Britain's War Machine demolishes timeworn myths about wartime Britain and gives us a groundbreaking and often unsettling picture of a great power in action"
"The familiar image of the British in the Second World War is that of the plucky underdog taking on German might. David Edgerton's bold, compelling new history shows the conflict in a new light, with Britain as a very wealthy country, formidable in arms, ruthless in pursuit of its interests, and in command of a global production system. Rather than belittled by a Nazi behemoth, Britain arguably had the world's most advanced mechanized forces. It had not only a great empire, but allies large and small. Edgerton shows that Britain fought on many fronts and its many home fronts kept it exceptionally well supplied with weapons, food and oil, allowing it to mobilize to an extraordinary extent. It created and deployed a vast empire of machines, from the humble tramp steamer to the battleship, from the rifle to the tank, made in colossal factories the world over. Scientists and engineers invented new weapons, encouraged by a government and prime minister enthusiastic about the latest technologies. The British, indeed Churchillian, vision of war and modernity was challenged by repeated defeat at the hands of less well-equipped enemies. Yet the end result was a vindication of this vision. Like the United States, a powerful Britain won a cheap victory, while others paid a great price."
1. Introduction -- 2. The Assurance of Victory -- 3. Never Alone -- 4. Cronies and Technocrats -- 5. Politics and Production -- 6. Sons of the Sea -- 7. Worlds of War -- 8. Boffins -- 9. Machines and Modernities.
Keywords: World War, 1939-1945 -- Great Britain; World War, 1939-1945 -- Economic aspects -- Great Britain; World War, 1939-1945 -- Technology; Industrial mobilization -- History -- 20th century -- Great Britain; Military art and science -- Technological innovations